Cyclic voltammetric behavior of crystal violet in aqueous solution: Correlation with dissolved states of cetyltrimethylammonium bromide (Journal of Bangladesh Academy of Sciences, 2024)
The cyclic voltammetric method was employed to study the electrochemical behavior of aqueous crystal violet in the presence of cetyltrimethylammonium bromide, both below and above the critical micelle concentration. The cyclic voltammograms were highly sensitive to solution pH exhibiting well-defined oxidation and reduction peaks within the pH range of 1.76 to 2.29. The electrochemical potentials and currents indicate the involvement of a set of reactions responsible for the observed voltammograms. The diquinoid of N, N, N’, N’- tetramethylbenzidine was formed, which was reduced to N, N, N’, N’- tetramethylbenzidine. The presence of CTAB profoundly influenced the electrochemical behavior, and responses were found to depend on the dissolved states of CTAB. The electrochemical process was diffusion-controlled and followed a chemical-electrochemical-chemical (CEC) mechanism.J. Bangladesh Acad. Sci. 48(1); 75-83: June 2024